Hardcourt : stories from 75 years of the National Basketball Association - Bowen, Fred (Margaret K. McElderry Books, 2022)
Provides a collection of illustrated stories about the National Basketball Association that describe pivotal moments in the league's history, including, how the league began, changes in scoring through the years, the acceptance of black players, famous rivalries, and the formation of the 1992 Dream Team.